Five new species of the Clubiona corticalis species group (Araneae, Clubionidae) from China - Liu, Ping; Peng, Xianjin; Yan, Hengmei (Zootaxa, 2016)
Five new species of the genus Clubiona collected in Mt. Gaoligong, Yunnan Province, China are described: C. biforamina n. sp., C. dactylina n. sp., C. falciforma n. sp., C. multidentata n. sp. and C. tangi n. sp., all belonging to the corticalis species group and known from both males and females.